Agrobiological features of the new naked oat variety Baget - G. A. Batalova; O. A. Zhuikova; N. V. Krotova; E. N. Vologzhanina; M. V. Tulyakova (Аграрная наука Евро-Северо-Востока, 2018)
Oat grain is used both for forage and food aims. Therefore, it is so important to grow naked oat that is more processable due to the lack of husk. Ten varieties of naked oat are included into the State Register of the breeding achievements of Russian Federation, but only three of them are suitable for growing in the European part of the country. That is why the aim of the study is creation of productive variety of naked oat having high grain qualities which would be suitable for growing in different agro-climatic zones of European Russia. Studies were conducted according to the methods of state varietal testing in three ecological sites: Federal Agricultural Scientific Center of North-East (Kirov, 2000 - 2017), Falenki breeding station - Branch of FARC North-East (v. Falenki, Kirov region, 2012 - 2017), and Samara Agricultural Research Institute ( Bezenchuk, Samara region, 2015 - 2017). Naked oat variety Baget was created by method of individual selection from cross population ОА 503/1 (Canada) * Tumensky golozerny (Russia) with following control of trait in further generations. The variety is intended for production of food grain (children, diet, functional, and gluten-free nutrition) as well as for grain forage. In 2017 there were the most favorable growing conditions for the vegetation of Baget variety and comparison varieties Vyatsky and Bekas within 2015 - 2017 studies. Index of environment conditions (lj) in 2017 varied from 0.734 in Samara and 0.7507 in Falenki breeding station up to 1.8274 in FARC North-East. Average productivity of the new variety for years of study in ecological sites was 4.07 t/ha that is 0.45 t/ha higher than for standard Vyatsky and 0.36 t/ha higher than for oat variety Bekas. Analogous data were received in studies of 2012-2017 for ecological sites of Kirov region. Exceed of standard on productivity (3.86 t/ha) was 0.48 t/ha, that of variety Bekas - 0.33 t/ha.